Clinical pharmaceutical analysis the treatment of hypertension in patients with diabetes mellitus in the hospital Mnazi Mnoja (Zanzibar) - V. А. Moroz (Zaporožskij Medicinskij Žurnal)
Treatment of arterial hypertension (AH) in patients with type II diabetes mellitus (DM) is a significant problem of practical medicine in many aspects.